Prevention of torture of persons deprived of liberty in Serbia: the State of affairs and challenges - Tanjević Nataša (Temida, 2019)
According to numerous international documents, the Constitution of the Republic of Serbia as well as relevant laws and by-laws related to the criminal justice system in general and the field of execution of criminal sanctions in particular, there is an absolute prohibition of torture, inhuman or degrading treatment or punishment and of inviolability of physical and psychological integrity od people. Thus, the most important international documents related to the prohibition of ill-treatment of persons deprived of liberty are analysed in the paper. Moreover, the aim of the paper is to determine the extent to which Serbian legislation complies with the international standards in this field. In order to identify possible shortcomings in this area and, consequently, the needs for improving the protection of persons deprived of liberty from torture, special attention is given to the role of independent monitoring mechanisms in the prevention of torture. This is particularly important if bearing in mind that the right to physical integrity and human dignity falls under the human rights category and that the prohibition of torture has a special status in international law and is treated as an imperative norm, thus, binding every state.